(untitled) - Dykes, Lucinda (New Jersey, 2005)
Tag -- XML is it! XML tags let you share your format as well as your data, and this handy guide will show you how. You'll soon be using this markup language to create everything from Web sites to business forms, discovering schemas and DOCTYPES, wandering the Xpath, teaming up XML with Office 2003, and more.
Keywords: XML ( document markup language )